2021
DOI: 10.3390/su13095018
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Technology to Learning-Teaching Processes and Google Workspace Tools: A Literature Review

Abstract: During the pandemic, educators around the world were unexpectedly encouraged to switch to online and distance learning. They tried to integrate face-to-face learning–teaching processes in the classrooms into the technological environment and to sustain this process in the best way. In this research, it is aimed to examine the current results in the current studies on technology integration into the teaching–learning processes in the literature. In order to collect data, a descriptive compilation pattern was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 30 publications
0
17
0
3
Order By: Relevance
“…Akcil, Uzunboylu and Kinik (2021), in their study during the pandemic period, aimed to examine the current results of existing studies on the integration of technology into teaching-learning processes in the literature, and as a result of the study, technology integration is a complex and multidimensional process with various dynamics and full integration is not possible [2]. They concluded that this study could not be achieved, if we set out in this study in the relevant research section, the model and method differ according to geographical location and student characteristics.…”
Section: Related Studiesmentioning
confidence: 99%
“…Akcil, Uzunboylu and Kinik (2021), in their study during the pandemic period, aimed to examine the current results of existing studies on the integration of technology into teaching-learning processes in the literature, and as a result of the study, technology integration is a complex and multidimensional process with various dynamics and full integration is not possible [2]. They concluded that this study could not be achieved, if we set out in this study in the relevant research section, the model and method differ according to geographical location and student characteristics.…”
Section: Related Studiesmentioning
confidence: 99%
“…The study is anchored to 5W1H Unified Integration Model. According to Akcil, et al (2021), the focus of this model is on student learning, and it is based on analyzing and planning the process to increase learning of students. The components consist of why (reasons), what (purposes), how (modes), who (people), where (places), and when (sequence/timing).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Además, la suite de Google está integrado a las aplicaciones externas como Youtube, Google Chrome, Blogger, y Búsquedas en Google (Google for Education, 2021). Dentro de las herramientas de la suite de Google más utilizadas en la educación son Google Drive, Classroom y Meet (Adkins at al., 2012;Akcil et al, 2021;Rusmansyah et al, 2021;Nina et al, 2017).…”
Section: Herramientas De Google En Procesos De Aprendizajeunclassified
“…Sin embargo, la migración no es fácil y requiere de competencias en tecnologías informáticas y adaptación de prácticas pedagógicas a un contexto virtual, tanto para docentes como para alumnos. En ese sentido, muchas instituciones educativas están en proceso de adaptación e integración de los procesos de enseñanza-aprendizaje presencial al entorno virtual y sostener este proceso de la mejor manera (Akcil et al 2021). Además, el proceso no es fácil puesto que en algunas zonas que no tienen acceso al Internet la adaptación es compleja o nula.…”
Section: Introductionunclassified
See 1 more Smart Citation